Answer:
8.06
Step-by-step explanation:
Hope it helps
Answer:
The answer is False
Step-by-step explanation:
Answer:
Solution given:
f(x) =
x-2
let f(x)=y
y =
x-2
interchanging role of x and y
x=
y-2
x+2=
y
y=9(x+2)
y=9x+18
So
<u>F</u><u>-</u><u>¹</u><u>(</u><u>x</u><u>)</u><u>=</u><u>9</u><u>x</u><u>+</u><u>1</u><u>8</u>
<u>a</u><u>n</u><u>d</u>
<u>F</u><u>-</u><u>¹</u><u>(</u><u>-</u><u>1</u><u>)</u><u>=</u><u>9</u><u>*</u><u>-</u><u>1</u><u>+</u><u>1</u><u>8</u><u>=</u><u>-</u><u>9</u><u>+</u><u>1</u><u>8</u><u>=</u><u>9</u>
Answer:
(9-j)-3
Step-by-step explanation:
Let's start from the beginning and subtract j from 9. Because the word "from" is used, 9 will be the first number and j will be the second number.
We have 9-j
Now, we have to subtract 3 from the final answer. So, we have (9-j)-3
Answer:
-3
Step-by-step explanation:
-2(2x+5)-x=5(x+1) +15
distribute
-4x-10-x=5x+5+15
add common terms
-5x-10=5x+20
move common terms to the same sides
-30=10x
divide
x=-3